Human Stem Cell Transplantation: An Overview Of The Islamic Perspective's Ethical Issues In Malaysia - Muhamad Rafiqi Hehsan; ‘Imran Mohd Pazudin; Muhammad ‘Afif Rosdin; Wan Athirah Wan Izudin; An Nisa Yustisia R; Nisya Oktia Nahdah; Zulkifli Dahalan (Penerbit USIM, 2024)
VOL. 28 NO. 3 (page: 1-20)